Mobile Forecast Weather station - Ameen Saleh; Rami Abid; Mohammad Khanfer (My University, 2013)
A wireless weather station is a standalone system that keeps the status of the outdoor temperature, humidity, daily amount of rainfall, barometric pressure, and wind speed; which is an outdoor weather monitoring system that gives easy way to keep the status of the outside weather. It has helped to travel safer without getting caught in bad weather condition like rain, snow, and fog. Wireless weather stations keeps us equipped with the weather report whenever and wherever. They are meant to give moment by moment information about changing of weather conditions. The main idea of this project is collecting information for weather conditions. Wireless weather substation being useful and portable. Weather forecasts is the most important services, which are used by government to protect life and property and to improve the efficiency of operations, and by individuals to plan a wide range of daily activities, today weather forecast is a highly developed that is based in scientific principle and method. The name of this project is Mobile Weather Forecast station, that means a mobile will be a meteorological station, so that mobile will receive measurements for some weather parameters as temperature, humidity, barometric pressure, wind speed and the daily amount of rainfall, mobile will receive all measurements by using GSM modem (the Global System for Mobile Communication) that will send data to it, so that it is very important idea that is grounded on the GSM modem which is very important in weather forecasts.   Block diagram for overall system                             This block diagram represents all measurements which will be taken from the weather by station. The core of this design is a microcontroller (Arduino Uno) which collects all data and sends it by using GSM modem to interface circuit that will be a mobile device.  The microcontroller will receive five measurements; one from these measurements is taken from rain gauge to measure the amount of rainfall, the rain gauge contains two parallel plate capacitors impacted along it, then the equivalent capacitance varies due to rainfall amount, the other measurements will be taken from four sensors; first sensor will read the temperature, second one read the humidity, and the last two sensors read speed of wind and barometric pressure.